Moral Decision-Making, Stress, and Social Cognition in Frontline Workers vs. Population Groups During the COVID-19 Pandemic: An Explorative Study - Mazza, Monica; Attanasio, Margherita; Pino, Maria Chiara; Masedu, Francesco; Tiberti, Sergio; Sarlo, Michela; Valenti, Marco (Frontiers in Psychology, 2020)
On March 9th 2020, Italy has gone into “lockdown” because of COVID-19 pandemic, with a national quarantine. All-nonessential working activities and schools of all levels have been temporarily closed: consequently, the entire population have been forced to dramatically change their daily habits. The pandemic raised important psychological, moral, social and economic issues. Our research focused on the moral decision-making of people during an emergency. This paper reports two studies. The aim of Study 1 was to evaluate moral decision-making, level of perceived stress, ability of mentalizing and empathy in university students and Italian workers. 224 front-line workers (FLW), 413 second-line workers (SLW), and 663 university students (US), during Italian Phase 1 of lockdown, completed an online questionnaire. The results of Study 1 showed that participants in the FLW group are more likely to choose utilitarian solutions and judge as morally acceptable actions finalized to saving lives of more people if this requires sacrificing a low number of individuals. At the same time, decision-making was experienced as less unpleasant and less arousing with respect to the other two groups, demonstrating a greater ability to keep emotional control under pressure. In Study 2, we compared the same variables used in Study 1, selecting two professional categories from the FLW group engaged in emergency during COVID-19, namely healthcare providers (n=82) and public safety personnel (n=117). Our results showed that healthcare providers were more stressed and emotionally involved than public safety personnel, with higher empathic concern and arousal in moral decision-making. We suggest it is essential providing immediate psychological support and monitoring physical and emotional well-being for workers in the front-line during emergencies like the COVID-19 pandemic, in order to prevent experiences of moral distress or mental health problems.